2020
DOI: 10.15560/16.5.1171
|View full text |Cite
|
Sign up to set email alerts
|

Crouania mageshimensis Itono, 1977 (Ceramiales, Rhodophyta) and three other species new to the Eastern Tropical Pacific

Abstract: We report new records of four macroalgae species in the Eastern Tropical Pacific, specifically from the rocky reefs of northern Chocó, Colombian Pacific. Among them, three species of Rhodophyta are included—Crouania mageshimensis Itono, 1977; Monosporus indicus Børgesen, 1931; Jania articulata N’Yeurt & Payri, 2009—and one species of Chlorophyta—Ulothrix subflaccida Wille, 1901. The new records increase the knowledge of tropical marine algae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Despite the progress made in the Caribbean Sea, the Pacific Ocean remains largely unexplored, mainly due to the difficulties of accessing certain oceanic zones, limiting the study of seaweeds to those associated with mangrove forests, which is the predominant ecosystem in the coastal areas of the Pacific [64,65]. The reports from the Pacific refer mainly to the work carried out by Schnetter and Bula-Meyer [66], Peña [67,68] and Rincón-Díaz et al [69,70] who identified approximately 203 species, whose taxonomic distribution is shown in Table 1. To date, studies on marine algal biodiversity in neighboring regions of the Pacific have focused mainly on Panama, Costa Rica, Nicaragua, Honduras, and Guatemala [71].…”
Section: Biodiversity Of Marine Algae In Colombiamentioning
confidence: 99%
“…Despite the progress made in the Caribbean Sea, the Pacific Ocean remains largely unexplored, mainly due to the difficulties of accessing certain oceanic zones, limiting the study of seaweeds to those associated with mangrove forests, which is the predominant ecosystem in the coastal areas of the Pacific [64,65]. The reports from the Pacific refer mainly to the work carried out by Schnetter and Bula-Meyer [66], Peña [67,68] and Rincón-Díaz et al [69,70] who identified approximately 203 species, whose taxonomic distribution is shown in Table 1. To date, studies on marine algal biodiversity in neighboring regions of the Pacific have focused mainly on Panama, Costa Rica, Nicaragua, Honduras, and Guatemala [71].…”
Section: Biodiversity Of Marine Algae In Colombiamentioning
confidence: 99%